Comparison Between Effect of Glimepiride and Pioglitazone on the C-Reactive Protein Level of Type 2 Diabetic Patient - Haque, AKM Fazlul; Haque, Md Zahirul; Ekram, ARM Saifuddin; Hoque, M Azizul; Islam, Quazi Tarikul (Journal of Medicine, 2011)
Background: This study was carried out to see the effect of glimepiride and pioglitazone on the serum hs-CRP level in type 2 diabetic patients. Material and Methods: A non-blind comparative study was conducted among 70 patients with type 2 diabetes (as per WHO criteria) divided into two groups (35 each) to see the effect of glimepiride and pioglitazone on their blood hs-CRP level. Results: 35 type-2 diabetic patients were given glimepiride. Another 35 patients were given pioglitazone. Fasting blood sugar, HbA1c%, hs-CRP and lipid profile were estimated before and 12 weeks after intervention. The mean change of serum hs-CRP was 1.13 mg/L to 0.76 mg/L in pioglitazone group. In glimepiride group the mean change of serum hs-CRP was 0.96 mg/L to 0.94 mg/L after 12 weeks. The change was greater in pioglitazone group in comparison to glimepiride group. Conclusion: Reduction of hs-CRP was significant in the study subjects revealing its future potential in reducing the vascular complications of type - 2 diabetes mellitus. Keyword: Type-2 diabetes; hs-CRP; Glimepiride; Pioglitazone; Cardiovascular complication DOI: 10.3329/jom.v12i1.6929 J Medicine 2011; 12 : 30-33